Advanced composite materials and manufacturing engineering : selected, peer reviewed papers from the 2012 International Conference on Advanced Composite Materials and Manufacturing Engineering (CMME2012) October 13-14, 2012, Beijing, China - Xu, B.; Li, H. Y. (Advanced materials research ;, 2012)
The proceedings of the International Conference on Advanced Composite Materials and Manufacturing Engineering (CMME2012), held on the 13 and 14 th October 2012 in Beijing, China, comprise 94 peer-reviewed papers grouped into: Advanced Composite Materials and Composite Properties of Materials; Materials and Mechanics Studies in Manufacturing Engineering; Materials Engineering and Materials Application Engineering. Review from Book News Inc.: Materials scientists, manufacturing engineers, and other contributors present 93 selected and peer-reviewed papers on such topics as the synthesis and perf.